Geology and sedimentary facies of the Pliocene succession of the Baronia Mountains (Ariano Basin, southern Italy). Issue 1 (1st January 2016) - Di Celma, Claudio; Rustichelli, Andrea; Tondi, Emanuele
Abstract : An up to 1500 m-thick clastic succession, the late Zanclean Baronia Synthem, has been analysed in detail in the Ariano wedge-top Basin (southern Apennine, Italy). In the Baronia Mountains the studied sediments are well exposed and laterally mappable due to young uplift and exhumation and rest unconformably on a complexly deformed pre-Pliocene substratum formed by Triassic to Miocene allochthonous units. The Baronia Synthem has been resolved into seven facies associations that are representative of distinct fluvial, deltaic, nearshore and offshore depositional environments and can be grouped into lowstand, transgressive, and highstand systems tracts. Using an integrated approach comprising original geological field mapping at 1:10, 000 scale, conventional sedimentary facies analysis and a sequence stratigraphic approach, this paper provides a detailed description and interpretation of facies associations and new insights on the stratigraphic architecture and the geological history of this portion of the basin fill.